Small Farm Food Safety, Fresh Produce: Part 2 - The Buck Stops Here - Brian Lapinski; Amy Simonne; Marilyn E. Swisher (EDIS)
FCS8843, a 6-page factsheet by Brian Lapinski, Amy Simonne, and M.E. Swisher, presents four different scenarios involving cases of foodborne illness causing unsafe food handling practices and provides discussion questions and analysis. Published by the UF Department of Family, Youth and Community Sciences, October 2007.